Étude expérimentale du séchage solaire des produits agroalimentaires de la région d'el-oued - مسعي أحمد, عبد الواحد; تماسيني, بشير (university of Eloued جامعة الوادي, 2018)
In this work, we are interested in solar drying of certain agro-food products, the most production in the el-oued region such as potato, red pepper and pea, using an indirect solar dryer. forced convection ,where the dryer used, the hot air which is provided by a parabolic concentrator oriented by means of a system of manual tracking of the sun, towards the drying chamber. this concentration model leads to temperature levels between 300-700 C The objective of this work is, on the one hand, the study of the drying kinetics of these three products and, on the other hand, the influence of the operating parameters on the drying time The experimental results shows that: the potato: the drying temperature ranging from (43-57), for the duration of 3h and the red pepper: the drying temperature ranging from (40-56), for the duration of 6 hours -and the pea: the drying temperature from (30-55), for the duration of 5h Finally, the interest of the drying process of these products is: the preservation of these products without used cold room. في هذا العمل نصب اهتمامنا على عملية تجفيف لعدة منتوجات غذائية زراعية الاكثر انتاجا في منطقة الوادي كالبطاطا والفلفل الاحمر وكذا الجلبانة حيث استعملنا في هذه التجارب مجفف شمسي قسري غير مباشر حيث في هذا الاخير يؤمن الحرارة لغرفة التجفيف بواسطة مركز شمسي مكافئ تصل درجة الحرارة التي يلتقطها على مستوى النقطة البؤرية من 300-700 درجة مئوية . الهدف الرئيسي من هذه التجارب هو دراسة حركية التجفيف من جهة والعوامل المطبقة على المنتوجات من جهة أخرى النتائج المتحصل عليها في هذه الدراسة التطبيقية لهذه المنتوجات كانت كالتالي : تتراوح درجة الحرارة المطلوبة من اجل تجفيف البطاطا من 43-57 درجة مئوية في ظرف 03 ساعات والفلفل الاحمر من 40- 56 درجة مئوية في ظرف 06 ساعات والجلبانة من 30-55 درجة مئوية في ظرف 05 ساعات . الفائدة من عملية التجفيف لهذه المنتجات هو المحافظة عليها بدون استعمال غرفة التبريد
مذكرة ماسترهندسة ميكانيكية تخصص طاقات متجددة
Keywords: : Solar drying, forced convection, solar dryer, parabolic concentrator, tracking system, red pepper, potato, kinetic drying pea, temperature; لقسري ’مركز مكافئ ’نظام متابعة يدوي ’البطاطا ’الفلفل الاحمر ’ الجلبانة’ حركية التجفيف ’الحرارة